2022
DOI: 10.36129/jog.2022.85
|View full text |Cite
|
Sign up to set email alerts
|

Does COVID-19 vaccination still have a role in maternal and perinatal outcomes during the Omicron era? A multicentre observational study

Abstract: Objective. COVID-19 vaccination has a reduced efficiency against the Omicron variant. The aim of this study was to assess the clinical impact of COVID-19 vaccination on maternal and perinatal outcomes during the Omicron wave. Materials and Methods.This was an observational multicenter study, pregnant women who gave birth while infected by SARS CoV2 during the Omicron waves were included.Patients with incomplete vaccination and recurrent infections were excluded. Patients were divided into 2 groups: the Vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In pregnancy, the American College of Obstetricians and Gynecologists recommended booster doses for pregnant and post-partum women on the basis of their increased risk of COVID-19-related complications [13]. Despite its safety, mothers are hesitant [14], and data on the durability of the immune response in pregnant women and the M a n u s c r i p t a c c e p t e d f o r p u b l i c a t i o n 9 SARS-CoV2 variants [3,6]. Several studies in the literature demonstrated the safety of the BNT162b2 second-and third-dose vaccines in pregnancy in terms of early adverse events and immunogenicity, as well as the absence of early obstetric complications [16,17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pregnancy, the American College of Obstetricians and Gynecologists recommended booster doses for pregnant and post-partum women on the basis of their increased risk of COVID-19-related complications [13]. Despite its safety, mothers are hesitant [14], and data on the durability of the immune response in pregnant women and the M a n u s c r i p t a c c e p t e d f o r p u b l i c a t i o n 9 SARS-CoV2 variants [3,6]. Several studies in the literature demonstrated the safety of the BNT162b2 second-and third-dose vaccines in pregnancy in terms of early adverse events and immunogenicity, as well as the absence of early obstetric complications [16,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…However, the new omicron variant of SARS-CoV2, which is M a n u s c r i p t a c c e p t e d f o r p u b l i c a t i o n dominating all over the world, is characterized by a modified spike protein structure which can lead to an increased risk of immune evasion with the reduced neutralizing activity of antibodies against this protein [3,4]. Recent doubts about the vaccines' efficiency against this variant were evoked [5], but other clinical studies showed that complete vaccination still plays a role in the improvement of outcomes [6]. In the general population, recent studies reported that primary COVID-19 vaccination efficacy was up to 90% within 6 months, decreasing rapidly to 34-80% after this period [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that vaccination during pregnancy improved obstetrical and neonatal outcomes by reducing the severity of COVID-19. [14][15][16] However, reports of rare but severe thrombotic events characterized by blood clots and low platelet counts after receiving some COVID-19 vaccines brought concerns about the safety of COVID-19 vaccines. [5][6][7][8][9][10] In this study, we first examined whether vaccination with inactivated COVID-19 vaccine before conception was associated with coagulation changes in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is the most effective way to decrease the severity of COVID‐19. It has been reported that vaccination during pregnancy improved obstetrical and neonatal outcomes by reducing the severity of COVID‐19 14–16 . However, reports of rare but severe thrombotic events characterized by blood clots and low platelet counts after receiving some COVID‐19 vaccines brought concerns about the safety of COVID‐19 vaccines 5–10 …”
Section: Discussionmentioning
confidence: 99%
“…Our study was limited by data from one hospital in China; thus, external validity in other medical centres is needed. In addition, it has been proven that providing complete vaccination is beneficial to improve maternal and neonatal outcomes (Jarraya, Kammoun, Kanoun, et al., 2022 ), yet the vaccination statuses of our subjects were not compared, considering a contraindication of pregnancy for the COVID‐19 vaccine recommended by the government at that time.…”
Section: Discussionmentioning
confidence: 99%